Motivation and Employee Performance in Hospital in Uganda: A Case of Kitgum General Hospital in Kitgum District. - Anenocan, Monica Oroma (Kabale University, 2024)
This study was conducted at Kitgum General Hospital, located in Kitgum Municipality in the Acholi sub-region of northern Uganda. It aimed to investigate the influence of motivational factors on employee performance in the hospital, guided by three specific objectives: to examine the motivational factors employed at the hospital, assess the level of employee performance, and explore the relationship between motivation and employee performance in the health sector. The study also addressed three research questions: What is the level of employee performance at the hospital? What motivational factors are used to enhance performance? What is the relationship between motivation and employee performance? The sample was selected using purposive and random sampling techniques, and both qualitative and quantitative data were collected. Qualitative data was gathered through interviews, coded, and organized according to the study's objectives. Quantitative data was collected using questionnaires and analyzed using descriptive statistics in Excel to interpret respondent profiles and their views on motivation and employee performance. The analysis aimed to determine the extent to which motivation influences performance at Kitgum General Hospital. The study concluded that motivating employees through financial incentives (such as rewards and contingent pay) and non-financial incentives (like recognition) significantly improves focus, productivity, and service delivery. This finding underscores the importance of motivation as a vital management tool for achieving high employee performance and organizational goals. Based on the data, the researcher recommended that hospital management should prioritize motivational factors such as timely rewards, recognition, and contingent pay aligned with the work performed by health workers. Such measures would encourage staff to work diligently and achieve organizational objectives while minimizing the need for supervision. Additionally, stakeholders, including the government, should organize workshops, seminars, and refresher courses to further enhance the skills and motivation of health workers.